The Relationship Between Self-Efficacy, Resilience, Meaning in Life, and Anxiety During the Crisis Situations - Widi Astuti; Maharani, Bintari Kartika; Cut Meurah Hadiah; Farah Yuliani; Fuadi, Fuja Simahara; Icha Lestari; Mellyana Br. Sembiring; Nurwafi Oktari; Rifda Hayati; Rio Zumaranto; Rusydina Sabila; Safrianti; Taufik Hidayat; Nur Afni Safarina; Maya Lestari (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2025)
This study examined the relationship between self-efficacy, resilience, meaning in life, and anxiety during crisis situations like the COVID-19 pandemic. Self-efficacy is considered an important psychological resource that supports individuals in coping with stressful and uncertain situations. Using a quantitative correlational design, data were collected from participants through standardized psychological scales measuring self-efficacy, resilience, meaning in life, and anxiety. Pearson correlation analysis was conducted to test the relationships among variables. The results indicated that self-efficacy was positively and significantly correlated with resilience and meaning in life, suggesting that individuals with higher confidence in their abilities tend to show stronger adaptive capacity and a greater sense of life meaning. In contrast, the relationship between self-efficacy and anxiety was negative but not statistically significant. Aspect-level analysis showed that the magnitude, strength, and generality dimensions of self-efficacy were consistently related positively to resilience and meaning in life. These findings highlight the protective role of self-efficacy in psychological functioning during crisis situations. The study contributes to the development of psychological intervention strategies by emphasizing the importance of strengthening self-efficacy and resilience to support mental health outcomes. Future research is recommended to apply longitudinal designs and include mediating variables to better explain these relationships